Analysis of the efficacy of antiepileptic drugs in the treatment of infantile spasms and focal epilepsy associated with tuberous sclerosis complex - A. V. Grigoryeva; M. Yu. Dorofeeva; V. S. Perminov; E. D. Belousova (Русский журнал детской неврологии, 2018)
Background. Adequate selection of the 1st antiepileptic drug (AED) is an obligatory condition for the successful treatment of epilepsy. It is well known that the first drug in the treatment of infantile spasms (IS) in tuberous sclerosis complex (TSC) is vigabatrin (VGB). With regard to focal seizures (FS) in TSC, there are certain differences: some authors insist on VGB (P. Curatolo, 2012), others as the first choice drugs are mentioning carbamazepine and valproate (A. Saxena, 2015). Data in general on the possible effectiveness of medical treatment of epilepsy in TSC, and the effectiveness of different AEDs are also contradictory.Objective: to make a comparative evaluation of the efficacy of various AEDs in the treatment of epilepsy in patients with TC.Materials and methods. Retrospective analysis of medical records of patients hospitalized with epilepsy and TSC in the Department of Epileptology and Psychoneurology, Research and Clinical Institute for Pediatrics named after Yu.E Vel’tishev of N.I. Pirogov Russian National Research Medical University, Ministry of Health of Russia, for the last 2 years was completed. Efficacy analysis was conducted in 134 patients (91 (67.9 %) with FS and 43 (32.1 %) with IS). Efficacy was estimated as the remission of epileptic seizures during 6 months. The percentage of patients with remission was also evaluated (seizures were stopped for 1 year or more) and percentage of patients with a decrease in the number of seizures. The results of the first monotherapy and the subsequent administration of two and three AEDs were analyzed.Results. Low efficiency of AEDs in starting monotherapy was noted – the remission of seizures within 6 months on any AED was only 27.5 % (25 from 91) with FS, with IS – 13.9 % (6 from 43). Remission on any 1st AED was observed only in 13.2 % (12 from 91) and 6.9 % (3 from 43), respectively. The effectiveness of individual AED is low, especially in achieving stable remission. So, valproate caused remission of FS in 14 (22.2 %) from 63, but in the future remission was stable only in 11 (17.5 %) from 63. VGB as the first monotherapy proved to be effective in 5 from 6 patients with FS and in 4 from 6 patients with IS. The introduction of the 2nd drug added another 13.3 % and 38.6 % of patients with remission of seizures, the 3rd AED – 7.3 % and 7.7 % in FS and IS, respectively. Most often, an effective drug in additional therapy was VGB. The efficiency of VGB was reduced if it was used not as the first, but as the second and third AED. The percentage of unsuccessful treatment (including combined therapy) is estimated as 51.5 % and 47.8 % of patients with FS and IS, respectively.Conclusion. Epilepsy associated with TSC is less sensitive to AEDs and gives a smaller percentage of remissions. Perhaps in our country this is due to the difficulties of prescription of VGB as a starting therapy for epilepsy in the patients with tuberous sclerosis complex.